King Shaka : Zulu legend - Molver, Luke W. (African graphic novel series., 2019)
King Shaka of the Zulu relates the tale of how the Zulu kingdom first defeated the slaver clans, only to encounter a new tide of colonization from foreign fortune-hunters from across the sea. Meanwhile, in Shaka's own land, treachery looms.